New insights for Drosophila GAGA factor in larvae. Issue 3 (March 2015) - Blanch, Marta; Piñeyro, David; Bernués, Jordi
Abstract : GAGA factor plays important roles during Drosophila embryogenesis and its maternal contribution is essential for early development. Here, the role of GAGA factor was studied in 3rd instar larvae using depletion and overexpression conditions in wing disc and transcriptome analysis. We found that genes changing expression were different to those previously described using GAGA mutants in embryos. No apparent phenotypes on GAGA depletion could usually be observed at larval stages in imaginal discs but a strong effect on salivary gland polytene chromosomes was observed. In the adult, GAGA depletion produced many defects like abnormal cell proliferation in the wing, impaired dorsal closure and resulted in homeotic transformation of abdominal segment A5. Unexpectedly, no effects on Ultrabithorax expression were observed. Short overexpression of GAGA factor in 3rd instar larvae also resulted in activation of a set of genes not previously described to be under GAGA regulation, and in lethality at pupa. Our results suggest a little contribution of GAGA factor on gene transcription in wing discs and a change of the genes regulated in comparison with embryo. GAGA factor activity thus correlates with the global changes in gene expression that take place at the embryo-to-larva and, later, at the larva-to-pupa transitions.